INTELLECTUAL PROPERTY RIGHTS VIOLATION IN VARIOUS ONLINEBUSINESS MODELS: A THOROUGH ANALYSIS - Nedelkovski, Boris (E-Journal VFU, 2024)
The paper studies the violation of intellectual property (IP) rights withindifferent online business models through a research that utilizes a comprehensive approach,including an introduction, methodology, online business model analyses, common IPinfringements, as well as in depth exploration of most impactful legal battles Viacom v.YouTube, A&M Records v. Napster, and Apple v. Samsung. The analysis extends to thechallenges faced in enforcing IP rights, detailing main challenges and key aspects.Additionally, the paper delves into legal responses and countermeasures, ranging from ceaseand desist letters to criminal prosecution, outlining enforcement mechanisms like WTO TRIPSand DMCA notices. Lastly, it delves into the future landscape of intellectual property (IP) rightsin online business models and discusses various emerging trends.
Keywords: Intellectual Property (IP) Law; Online Business Models, IP Infringement; Viacom v. YouTube; A&M Records v. Napster; Apple v. Samsung; Enforcement Challenges; Legal Responses